Rapid Antidepressant and Antisuicidal Effects of Low-Dose Ketamine Infusion in Patients With Treatment-Resistant Depression With or Without Low-Grade Inflammation - Chen, Mu-Hong; Su, Tung-Ping; Lin, Wei-Chen; Li, Cheng-Ta; Wu, Hui-Ju; Tsai, Shih-Jen; Bai, Ya-Mei; Mao, Wei-Chung; Tu, Pei-Chi (Pharmacopsychiatry, 2024)
Low-grade inflammation (LGI) contributes to resistance against traditional antidepressants. However, whether the antidepressant and antisuicidal effects of ketamine on patients with treatment-resistant depression (TRD) differ between those with LGI and those without LGI remains unknown.This study included 167 patients with TRD, among whom 46 had LGI and 121 did not have LGI. The patients received a single infusion of either low-dose ketamine or a placebo. A C-reactive protein level of≥3 mg/L indicated LGI. Depressive symptoms were measured from baseline to day 3 by using the 17-item Hamilton Depression Rating Scale (HDRS) and the Montgomery-Asberg Depression Rating Scale (MADRS).Generalized estimating equation models revealed antidepressant effect of ketamine in patients with no LGI (HDRS scores: p<0.001; MADRS scores: p<0.001) but not in patients with LGI (all p>0.05). The antisuicidal effect of ketamine (indicated by the score on item 10 of the MADRS) was observed in both groups of patients with (p=0.046) and without LGI (p<0.001). However, ketamine was effective for TRD regardless of whether inflammation levels were high or low, while the placebo response was notably greater only in patients with LGI.This study suggests that among patients with TRD, only those without LGI respond to low-dose ketamine infusion. Whether the negative findings of the antidepressant effect of ketamine among patients with LGI may be because of the effect of the placebo infusion needs further investigation. Further randomized, placebo-controlled studies are needed to validate these findings.
Keywords: low-grade inflammation; ketamine; antidepressant effect; antisuicidal effect